2020
DOI: 10.1021/jacs.0c05951
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Thermal Hysteresis of Single Spin-Crossover Nanoparticles

Abstract: The magnetic hysteresis property during the spin transition of spin-crossover (SCO) materials holds great promise for their applications in spin electronics, information storage, thermochromic, and nanophotonic devices. Existing studies often measured the averaged property of a bulk sample consisting of lots of individuals. When considering the significant heterogeneity among different individuals and the inevitable interparticle interactions, ensemble measurement not only blurred the structure−property relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…Indeed, the knowledge of the exact volume change of a single SCO particle, its time scale upon photo-switching and its repeatability is of importance to understand the transport mechanisms, the occurrence of percolation effect (when the increase of volume induces nanoparticles to be in contact) and the fatigue of the devices. A recent study has shown the thermal hysteresis loop and LS to HS switching kinetic at the second time scale on individual nanoparticles through optical methods without providing information on the volume change 44 . In a previous investigation [45,46] , ultrafast TEM has already shown shape changes of SCO particles after laser irradiation, but details of this transformation and the influence of embedded plasmonically active particles remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the knowledge of the exact volume change of a single SCO particle, its time scale upon photo-switching and its repeatability is of importance to understand the transport mechanisms, the occurrence of percolation effect (when the increase of volume induces nanoparticles to be in contact) and the fatigue of the devices. A recent study has shown the thermal hysteresis loop and LS to HS switching kinetic at the second time scale on individual nanoparticles through optical methods without providing information on the volume change 44 . In a previous investigation [45,46] , ultrafast TEM has already shown shape changes of SCO particles after laser irradiation, but details of this transformation and the influence of embedded plasmonically active particles remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Here we primarily refer to OM in bright-field, transmission mode, which probes local absorbance changes and allows for quantitative spatiotemporal studies of the spin-state transformation. It should be noted, however, that OM has been also used to probe refractive index and luminescence intensity changes, enabling to detect the spin transition in single SCO micro-nano-particles [6][7][8]).…”
Section: Introductionmentioning
confidence: 99%
“…Single nanoparticles induce the localized enhancement of SPPs, and transforms to far field via leakage radiation for fast and label-free detection [5,6]. This method has been widely applied to chemistry and biology, such as bidirectional electron transfers visualizing [7], local activation energy barrier measuring [8], thermal hysteresis imaging of single spin-crossover nanoparticles [9], and single liposomes and virus detection [10][11][12].…”
Section: Introductionmentioning
confidence: 99%